Normal temperature catalytic degradation of toluene over Pt/TiO2. Issue 13 (7th June 2022) - Liu, Rui; Tian, Mingze; Shang, Wei; Cui, Jiahao; Zhao, Dan; Liu, Shejiang; Zhao, Yingxin; Ding, Hui; Fu, Jianfeng
ABSTRACT: Normal temperature catalytic ozonation is an effective method for the removal of volatile organic compounds (VOCs). A series of TiO2 -supported noble metal catalysts were synthesized by a facile impregnation method. The as-prepared catalysts were evaluated for the catalytic oxidation of toluene. It was determined that the 1 wt%Pt/TiO2 exhibited outstanding performance that 65% conversion of toluene was achieved with the space velocity of 30, 000 h −1 even at room temperature (25°C). The structure–activity relationship of various catalysts was investigated via BET, XRD, SEM, TEM as well as XPS. The results indicated that the uniform dispersion of Pt nanoparticles, abundant surface adsorbed oxygen species as well as the strong interaction between Pt and TiO2 favoured toluene degradation at normal temperature. Based on FT-IR, a simplified reaction scheme was proposed: toluene was first oxidized to benzoate species then alcohol species, ketones, carboxyl acids, which was finally degraded into CO2 and H2 O. The low activation energy of 1 wt%Pt/TiO2 determined to be 47 kJ mol −1 also benefited for toluene degradation at ambient temperature. GRAPHICAL ABSTRACT: UF0001